Biological features on epibiosis of Amphibalanus improvisus (Cirripedia) on Macrobrachium acanthurus (Decapoda) (Brazilian Journal of Oceanography, 2010)
This study aimed to describe the epibiosis of barnacles Amphibalanus improvisus on eight adult Macrobrachium acanthurus males from the Mundaú Lagoon, state of Alagoas, Brazil. The number of epibiont barnacles varied from 247 to 1,544 specimens per prawn; these were distributed predominantly on the cephalothorax and pereiopods, but also on the abdomen and other appendices. Although some were already reproducing, most barnacles had been recruited recently or were still sexually immature; this suggests recent host arrival in that estuarine environment. Despite the fact that other barnacles occur in this region, A. improvisus is the only species reported as an epibiont on Macrobrachium acanthurus; this was also the first record of epibiosis on this host. The occurrence of innumerable specimens in the pereiopods' articulations and the almost complete covering of the carapace of some prawns (which also increased their weight) suggest that A. improvisus is adapted to fixate this kind of biogenic substrate and that the relationship between the two species biologically damages the basibiont.